Intraoperative diagnostic and interventional MRI in neurosurgery: first experience with an “Open MR” system - Albert, Friedrich; Wirtz, Christian Rainer; Tronnier, Volker; Hamer, Jürgen; Bonsanto, Matteo Mario; Staubert, Andreas; Knauth, Michael; Kunze, Stefan (Minimally invasive techniques for neurosurgery, 1998)
In December 1995, an “open MRI” unit was installed inside a radiofrequency cabin adjacent to one of the operating theatres at the Department of Neurosurgery, University Hospital, Heidelberg College of Medicine. Since then, 60 open intra-cerebral procedures have been performed using this scanner for three main applications of intra-operative diagnostic and interventional MRI (IODIM):1.Resection control of brain tumours2.On-line guidance for stereotactic interventions (e. g. biopsy, cyst aspiration, catheter placement3.Acquisition of actual data for the intraoperative update of neuronavigationOur first results show that IODIM provides an additional support for the neurosurgeon to improve the efficiency of tumour ablation and of targeting deep-seated structures in order to manipulate them under visual control. Furthermore, it is a reliable method of intraoperatively updating the neuronavigational dataset.
Gesehen am 2207.2025